Wpływ praktyki szkolnej na kształtowanie samodzielnego osiągania sukcesów w matematyce - Alayan, Rowaidah (Studia Edukacyjne, 2018)
The purpose of this article is to specify whether there is any influence of school practices towards mathematics self-efficacy and mathematics outcomes. The studies about the effect of school practice on student achievement have a long history both domestically and abroad. However, the investigation of how the social context of school and practices affect student performance is not clear, especially in mathematics. To investigate this, I will chose al-touri secondary school where I teach as a case-study for my research. The instrument use for the article will be based on a questionnaire, which contains 2 sections. Section 1 will contain “School Level Environment Questionnaire” (SLEQ). Section 2 will contain “Mathematic Self-efficacy Questionnaire” (MSEQ). The mathematic scores of students will be taken for the first and second semester to compare between them and to see if there is a significant relationship between school practices and mathematics self-efficacy and mathematics outcomes. The findings indicate that there is a significant difference in students’ perception about their school practice and mathematic self-efficacy based on their achievement and according to ANOVA test, there is a relationship between school practices and mathematic self-efficacy. The result from this study can be generalized to the population of all schools in the Arab Sectors in Israel. Moreover, we can use the questionnaires obtained in the study to identify the strengths and weaknesses of schools in their teaching and learning process and to focus on improving their latter, at the same time maintaining the strength of their teaching strategies.